KECELAKAAN KONSTRUKSI DAN KEGAGALAN BANGUNAN: PARADIKMA BARU KESELAMATAN KONSTRUKSI DAN PENERAPAN SESUAI REGULASI - Ali Amal (LPPM, 2023)
ABSTRACT The number of construction accidents and construction building failures in Indonesia is quite high, from 2017 to 2020 there were 40 construction accidents, and there were 9 construction building failures. Construction accidents and building failures are generally caused by factors not fulfilling the construction engineering standards which have an impact on labor accidents, equipment, materials, environment and public. This study aims to find out the new pradikma of construction safety and its application in accordance with regulations with data collection and analysis methods in literature studies and observations, data comes from journals, books or the results of discussions Focus Group Discussion (FGD) Construction Safety, laws and regulations as a basis for thinking, The Ministry of Public Works and Public Housing as asupervisor for construction service providers in Indonesia, has tried to minimize or eliminate the problem of constructin accidents and buiding failures, through the National Movement for Construction Safety Program implemented by the Construction Safety Committee and the Construction Building Safety Commission, through Construction Safety actions with monitoring and evaluation activities related to compliance with safety standards, safety, health and sustainability standards (Standard K4), which includes material quality standards, equipment quality standards, standard K3, standard procedures for the implementation of Construction Services, quality standards for the implementation of Construction Services, operation and maintenance standards, standard guidelines for social protection for workers in the implementation of Construction Services, environmental management standard, and management using collaborative construction resources, comprehensive and integrated construction work objects with a new paradigm of construction safety then there will be a safety first and zero accident development work environment..